Modulation of auditory evoked magnetic fields elicited by successive frequency-modulated (FM) sweeps - Okamoto, Hidehiko; Kakigi, Ryusuke (Frontiers in Human Neuroscience, 2017)
In our daily life, we are successively exposed to frequency-modulated (FM) sounds that play an important role in speech and species-specific communication. Previous studies demonstrated that repetitive exposure to identical pure tones resulted in decreased neural activity. However, the effects of repetitively presented FM sounds on neural activity in the human auditory cortex remain unclear. In the present study, we used magnetoencephalography to investigate auditory evoked N1m responses elicited by four successive temporally repeated and superimposed FM sweeps in three sequences: 1) four FM sweeps were identical, 2) four FM sweeps had the same FM direction and rate, but different carrier frequencies, 3) four FM sweeps differed with respect to the FM rate and/or direction and their carrier frequencies. In contrast to our expectations, the results obtained demonstrated that N1m responses were maximal when the four FM sweeps were identical and minimal when they were distinct. These results suggest that the neural processing of repetitive FM sweeps in the human auditory cortex may differ from that of repetitive pure tones.